2008
DOI: 10.1139/w08-035
|View full text |Cite
|
Sign up to set email alerts
|

Oxylipin and mitochondrion probes to track yeast sexual cells

Abstract: When oxylipin and mitochondrion probes, i.e., fluorescing antibodies specific for 3-hydroxy fatty acids (3-OH oxylipins) and rhodamine 123 (Rh123), were added to yeast cells, these probes accumulated mainly in the sexual cells (i.e., both associated with ascospores) and not in the vegetative cells. This suggests increased mitochondrial activity in asci, since 3-OH oxylipins are mitochondrially produced and it is known that Rh123 accumulates selectively in functional mitochondria that maintain a high transmembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A separate study found EMA treatment at concentrations of 10 to 25 µg mL -1 , followed by a 2 minute halogen light exposure, yielded successful qPCR of DNA from viable E. coli cells (Inoue et al, 2008). Cleland et al (2008) In order to detect cells with mitochondrial activity, fluorescing antibodies specific for 3-hydroxy fatty acids (3-OH) oxylipins, which are mitochondriallyproduced, and rhodamine 123 (Rh123), which accumulate in functional mitochondria, were successfully added to a culture of yeast cells to detect reproducing cells (Ncango et al, 2008).…”
Section: Other New Methodsmentioning
confidence: 99%
“…A separate study found EMA treatment at concentrations of 10 to 25 µg mL -1 , followed by a 2 minute halogen light exposure, yielded successful qPCR of DNA from viable E. coli cells (Inoue et al, 2008). Cleland et al (2008) In order to detect cells with mitochondrial activity, fluorescing antibodies specific for 3-hydroxy fatty acids (3-OH) oxylipins, which are mitochondriallyproduced, and rhodamine 123 (Rh123), which accumulate in functional mitochondria, were successfully added to a culture of yeast cells to detect reproducing cells (Ncango et al, 2008).…”
Section: Other New Methodsmentioning
confidence: 99%
“…Liu and colleagues (2008) In order to detect cells with mitochondrial activity, fluorescing antibodies specific for 3-hydroxy fatty acids (3-OH) oxylipins, which are mitochondriallyproduced, and rhodamine 123 (Rh123), which accumulate in functional mitochondria, were successfully added to a culture of yeast cells to detect reproducing cells (Ncango et al, 2008).…”
Section: Other New Methodsmentioning
confidence: 99%
“…Tel: +27 51 401 2249. Fax: +27 401 9376. in most ascomycetous yeasts except in Zygosaccharomyces (Kock et al, 2007;Ncango et al, 2008;Swart et al, 2008Swart et al, , 2010a.…”
Section: Introductionmentioning
confidence: 99%